The 'breaking the chains' migration model for super-Earth foation: The effect of collisional fragmentation - Esteves, Leandro [UNESP]; Izidoro, André [UNESP]; Bitsch, Bertram; Jacobson, Seth A; Raymond, Sean N; Deienno, Rogerio; Winter, Othon C [UNESP] (Oxford University Press (OUP), 2022)
Planets between 1 and 4 R (Earth radius) with orbital periods <100 d are strikingly common. The migration model proposes that super-Earths migrate inwards and pile up at the disc inner edge in chains of mean motion resonances. After gas disc dispersal, silations show that super-Earth's gravitational interactions can naturally break their resonant configuration leading to a late phase of giant impacts. The instability phase is key to matching the orbital spacing of observed systems. Yet, most previous silations have modelled collisions as perfect accretion events, ignoring fragmentation. In this work, we investigate the impact of imperfect accretion on the 'breaking the chains' scenario. We perfoed N-body silations starting from distributions of planetary embryos and modelling the effects of pebble accretion and migration in the gas disc. Our silations also follow the long-te dynamical evolution of super-Earths after the gas disc dissipation. We compared the results of silations where collisions are treated as perfect merging events with those where imperfect accretion and fragmentation are allowed. We concluded that the perfect accretion is a suitable approximation in this regime, from a dynamical point of view. Although fragmentation events are common, only 10 per cent of the system mass is fragmented during a typical 'late instability phase', with fragments being mostly reacreted by surviving planets. This limited total mass in fragments proved to be insufficient to alter qualitatively the final system dynamical configuration - e.g. promote strong dynamical friction or residual migration - compared to silations where fragmentation is neglected.
Keywords: foation; planets and satellites; protoplanetary discs